Impact of Disease Activity on the Quality of Life of Crohn’s Disease Patients - T Michael Vallis; Geoffrey K Turnbull (Canadian Journal of Gastroenterology)
Crohn’s disease (CD) patients often suffer severe symptoms that impair their quality of life. A sample of 39 CD patients who were assessed using well validated measures of disease activity and disease-specific quality of life is reported. Twenty-six of these patients were reassessed an average of four months after the initial assessment to determine the impact of changes in disease activity on quality of life. For the total sample (n=39) disease activity did not predict quality of life for any of the scales of the Inflammatory Bowel Disease Questionnaire (IBDQ) (r<0.13 for each). Thus, examining fluctuations in disease activity between patients did not demonstrate a disease activity-quality of life relationship. In contrast, changes in disease activity within the same individuals over time (the repeat assessment sample, n=26) were correlated with changes in quality of life; increases in disease activity predicted decreases in quality of life on the IBDQ bowel symptoms subscale (r=-0.463, P<0.01) and the IBDQ systemic symptoms subscale (r=0.44, P<0.05). The 10 patients with the largest decrease in disease activity over time (mean decrease of 43.54 points using the Dutch Activity Index) had significant improvement in quality of life on the bowel and systemic subscales. In contrast, the nine patients with the largest increase in disease activity over time (mean increase of 20.57 points using the Dutch Activity Index) had significant reduction in quality of life on the bowel and systemic symptoms subscales. These differences between extreme groups were significant for both the bowel symptoms (P<0.05) and systemic symptoms (P<0.05) subscales. The authors conclude that changes in disease activity affect some important aspects of quality of life: aspects related to disease-specific (bowel symptoms) and nondisease-specific (systemic symptoms) physical symptoms. Importantly, disease activity was not able to predict the emotional and social aspects of IBD-related quality of life. This suggests that nondisease factors need to be considered when working with CD patients. Future research should evaluate the role of psychological intervention in improving quality of life for patients with reduced well-being, particularly in areas of emotional and social functioning.